THE ABILITY OF Chorella sp. ON REDUCING Zn CONSENTRATION OF SWEATER IN LABORATORY - Tri Hastutiningsih; Tri Retnaningsih Soeprobowati; Hendarko Sugondo (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Research on the use of Chorella sp. on reducing of Zn concentrations was conducted in order to know Zn concentration which is maximally absorbed by Chorella sp. In the preliminary experiment, there was the range of Zn concentration that caused the highest population growth of Chorella sp. was 0.1 – 0.4 ppm. In the main experiment, it was divided into five concentrations and one control with three replications. Each of concentrations was treated on Chorella sp. culture with the first Zn concentration (0.0042 ppm) in the medium culture. Those concentrations were 0.05 ppm, 0.15 ppm, 0.35 ppm, 0.45 ppm. All of the concentrations were given on the day of 5. The density of cells which was used for each flask was 100,000 cells/ml. The fertilizers used for each flask were : ZA, Urea, TSP, FeCl3, EDTA. The result showed that there was an interaction between the population growth of Chorella sp. and the reducing of Zn concentration. The highest population growth of Chorella sp. was found in the treatment of 0.15 ppm Zn concentration.